2018
DOI: 10.3390/ijerph15051004
|View full text |Cite
|
Sign up to set email alerts
|

The Radon Gas in Underground Buildings in Clay Soils. The Plaza Balmis Shelter as a Paradigm

Abstract: In healthy buildings, it is considered essential to quantify air quality. One of the most fashionable indicators is radon gas. To determine the presence of this element, which is harmful to health, in the environment, the composition of the soil is studied. The presence of radon gas within a building depends both on the terrain in which it is located and on the composition of the materials of which it is composed, and not as was previously believed, only by the composition of the soil (whether granitic or not)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…The shelter has been studied in different aspects: the constructive typology of the underground building, its historical context, and the presence of radon inside was measured using rigorous measurement techniques. The results obtained from the measurements make the shelter a paradigm to demonstrate the relevant presence of more than 100 Bq/m 3 of radon in the interior of an underground building in non-granitic soil [40].…”
Section: Radon Gas In Alicantementioning
confidence: 95%
“…The shelter has been studied in different aspects: the constructive typology of the underground building, its historical context, and the presence of radon inside was measured using rigorous measurement techniques. The results obtained from the measurements make the shelter a paradigm to demonstrate the relevant presence of more than 100 Bq/m 3 of radon in the interior of an underground building in non-granitic soil [40].…”
Section: Radon Gas In Alicantementioning
confidence: 95%
“…Barré et al, 2008;Milošević et al, 2017;Tarvainen et al, 2005), and although the permeability of wet clays is low, it may increase when soils are dried (Petersell et al, 2005) as a consequence of building a house (Barnet et al, 2008). This hypothesis should be tested since clay soils are normally considered low risk although its radium concentration may be high (Maestre and Iribarren, 2018). We have decided, however, to include this parameter in the model since previous studies have shown a positive association between indoor radon and K 2 O/clay (Forkapic et al, 2017).…”
Section: Indoor Radon Predictionsmentioning
confidence: 99%
“…However, the E[X] and Var[X] for CCK and RK are biased, unless the true mean is known (although for RK it should be zero by definition). These equations should also use the Lagrange multiplier which appears in the kriging system (Chilès and Delfiner, 1999;Matheron, 1974); but unfortunately in common geostatistical packages this parameter is not accessible, and it is not easy to estimate it. Another problem with lognormal kriging is that ill assessment of the kriging SD leads to large errors in E[X] and Var[X] due to exponentiation, so that variogram parameters must be estimated very carefully (Armstrong and Boufassa, 1988).…”
Section: Indoor Radon Predictionsmentioning
confidence: 99%
“…In the urban center of the city are the two mountains compared in the study: Benacantil Mount and Serra Grossa. Therefore, they can be considered to have the same igneous composition [45,46].…”
Section: Radon Gas As An Indicator Of Ventilationmentioning
confidence: 99%